A Systematic Review on the Impact of Gender Equity on Educational Leadership - Laki, Reniel C.; Badon, Benjie O. (Jurnal Multidisiplin Madani, 2024)
People have often discussed about whether men or women are better leaders. This ongoing discussion has led to debates and theories about male and female leadership. It shows that many are still curious about how being male or female might affect someone’s leadership style. In educational institution, leaders deal with a lot of changes in a constantly changing and competitive environment. This study reviews the effects of gender equity on educational leadership, which focuses specifically on how it influences leaders regardless of gender. After conscientious evaluation guided by the review protocols, 12 were finally selected from the initial 436 articles. The findings indicate that gender equity fosters a variety of perspectives and strengths in both male and female leaders, enriching decision-making processes and promoting innovation. Moreover, it helps in reducing biases and creating a more inclusive environment, benefiting individuals of all genders. The review emphasizes the significance of promoting gender diversity in leadership positions for the overall improvement of educational. Further, it is recommended for extensive research not limited to identifying the common challenges and experiences face by leaders in both genders. Hence, this review put emphasize on the essence and significance of gender equity to the leaders in every educational institution that will result for a more creative and inclusive learning environment to achieve it common organization objective